2022
DOI: 10.3389/fgene.2022.1024508
|View full text |Cite
|
Sign up to set email alerts
|

A panel of seven immune-related genes can serve as a good predictive biomarker for cervical squamous cell carcinoma

Abstract: Objective: Cervical cancer is one of the most common gynecological malignancies. The interaction between tumor microenvironment and immune infiltration is closely related to the progression of cervical squamous cell carcinoma (CSCC) and patients’ prognosis. Herein, a panel of immune-related genes was established for more accurate prognostic prediction.Methods: The transcriptome information of tumor and normal samples were obtained from TCGA-CSCC and GTEx. Differentially expressed genes (DEGs) were defined from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…BAIAP2L1 is notably overexpressed in various malignancies including breast cancer [ 33 ], ovarian cancer [ 34 ], gastric cancer [ 35 ], lung cancer [ 36 ], and hepatocellular cancer [ 37 ], where its higher expression correlates with advanced disease stages and metastasis [ 33 , 34 , 38 , 39 ]. Similarly, NRP1, which is abundantly expressed across a range of tumors such as glioma [ 40 ], bladder cancer [ 41 ] and cervical cancer [ 42 ], is linked with unfavorable outcomes. These findings align with prior research, reinforcing the critical role of NRP1 in processes such as embryonic angiogenesis and neurogenesis—mechanisms essential for cell migration, proliferation, survival, and apoptosis [ [43] , [44] , [45] ].…”
Section: Discussionmentioning
confidence: 99%
“…BAIAP2L1 is notably overexpressed in various malignancies including breast cancer [ 33 ], ovarian cancer [ 34 ], gastric cancer [ 35 ], lung cancer [ 36 ], and hepatocellular cancer [ 37 ], where its higher expression correlates with advanced disease stages and metastasis [ 33 , 34 , 38 , 39 ]. Similarly, NRP1, which is abundantly expressed across a range of tumors such as glioma [ 40 ], bladder cancer [ 41 ] and cervical cancer [ 42 ], is linked with unfavorable outcomes. These findings align with prior research, reinforcing the critical role of NRP1 in processes such as embryonic angiogenesis and neurogenesis—mechanisms essential for cell migration, proliferation, survival, and apoptosis [ [43] , [44] , [45] ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study have shown that NRP1 was associated with cervical cancer progression and poor survival, suggesting that NRP1 could be an independent prognostic factor in cervical cancer [ 54 ]. High expression of NRP1 in cervical cancer patients was correlated with shorter OS [ 55 ]. Moreover, preoperative chemoradiation therapy reduced Treg and Nrp1 + Treg levesl in lymph nodes of cervical cancer patients [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXC chemokines exert promotive or suppressive effects on tumors by recruiting different immune cell types to specific tumor sites. Furthermore, chemokines can influence tumor cell proliferation, metastasis, and stromal cell biology, participating in the generation and metastasis of tumor vessels [12][13][14].…”
Section: Introductionmentioning
confidence: 99%